Observations of expert communicators in immersive virtual worlds: implications for synchronous discussion - Michael Hamilton McVey (Association for Learning Technology, 2008)
With the increased interest in using Immersive Virtual Worlds (IVWs) such as Second Life to augment and amplify teaching or to develop communities of practice, the author engaged graduate students, all current K-12 teachers, in a qualitative study to examine their attitudes about communicating for the first time in a virtual setting represented by an interactive avatar. This study sought to determine if students were able to discern degrees of expertise in other avatars by providing encounters with guests who had a significant amount of experience navigating in a virtual world. The study examined Second Life as a synchronous discussion tool for a higher education setting and finds it lacking in some respects, but is able to make recommendations about training instructors to exhibit behaviours that may inspire confidence while leading a class in such a setting.